Diastereo‐ and Enantioselective Synthesis of Organometallic Bis(helicene)s by a Combination of CH Activation and Dynamic Isomerization. Issue 49 (31st October 2013) - Shen, Chengshuo; Anger, Emmanuel; Srebro, Monika; Vanthuyne, Nicolas; Toupet, Loïc; Roussel, Christian; Autschbach, Jochen; Réau, Régis; Crassous, Jeanne
Abstract Homochiral and heterochiral cis‐bis‐cycloplatinated‐[6]helicene derivatives 1 b1, 2, as representative examples of platina[6]helicenes that share a common platinum center, have been prepared. A diastereo‐ and enantioselective synthesis, which combines CH activation and dynamic isomerization from heterochiral structure 1 b2 into homochiral structure 1 b1, is also described. Overall, this isomerization process results in the transfer of chiral information from one helicene moiety to the other one. The chiroptical properties of homochiral (P)‐ and (M)‐1 b1 were greatly modified upon oxidation into their corresponding (P)‐ and (M)‐diiodo‐PtIV complexes (5). The changes were also analyzed by performing theoretical calculations. CH activation in the synthesis of organometallic helicenes is further demonstrated by the preparation of cis‐bis‐cycloplatinated‐[8]helicene 1 c.